Mental health and Multiracial/ethnic adults in the United States: a mixed methods participatory action investigation - Shaff, Jaimie; Wang, Xinzi; Cubbage, Janel; Bandara, Sachini; Wilcox, Holly C. (Frontiers in Public Health, 2024)
Introduction Addressing gaps in the integration of justice, diversity, equity, and inclusion (J-DEI) in public health research and practice, this study investigates the mental health of Multiracial and multiethnic adults in the United States (U.S.). A rapidly growing racial/ethnic group in the U.S., Multiracial and multiethnic populations are often excluded or underrepresented in standard public health research and practice, and little is known about their mental health or associated risk and protective factors. Methods To investigate this knowledge gap, an electronic cross-sectional survey was conducted in two waves in 2022, pulling from various community sources, with 1,359 respondents in total. Complementing this, seventeen semi-structured interviews were performed with a subset of survey participants. Data were analyzed using a mix of statistical methods and staged hybrid inductive-deductive thematic analysis. Results Findings indicate over half of the participants endorsed at least one mental health concern with prevalence of anxiety, depression, post-traumatic stress disorder, and suicidal thoughts and behaviors surpassing available national estimates. Exposure to trauma, discrimination, and microaggressions were found to play a significant role in these outcomes. Conversely, strong social support and strong ethnic identity emerged as protective factors. Qualitative insights brought forward the challenges faced by individuals in navigating bias and stigma, especially in the context of mental health care. Despite these barriers, emerging themes highlighted resilience, the importance of secure identity formation, and the critical role of community and cultural support. Conclusions The marked prevalence of mental health concerns among Multiracial and multiethnic populations emphasizes the pressing need for tailored interventions and inclusive research methodologies. Recognizing and addressing the unique challenges faced by these communities is imperative in driving mental health equity in the U.S. The findings advocate for community-engaged practices, interdisciplinary collaborations, and the importance of addressing mental health challenges with cultural sensitivity, particularly in historically oppressed and marginalized groups. Future efforts must focus on refining these practices, ensuring that public health initiatives are genuinely inclusive and equitable.